2014
DOI: 10.1590/s1516-35982014000900008
|View full text |Cite
|
Sign up to set email alerts
|

Management factors and cow traits influencing milk somatic cell counts and teat hyperkeratosis during different seasons

Abstract: -The objective of the study was to analyze the effect of season, parity, stage of lactation and milking procedures on teat-end condition, cow cleanliness and milk somatic cell count (SCC) and identify risk factors associated with milk somatic cell counts greater than 100,000 cells/mL. A group of 15 Italian dairy farms were visited three times during different seasons: the cold (3.8 °C), the hot (23.5 °C) and the mild (12.1 °C) seasons. Hygiene of udder, flanks and legs was scored on 2,330 cows based on a 4-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
5
15
1
Order By: Relevance
“…There was an increase in the percentage of leg 3 + 4 scores from 27·1% in the first year to 49·9% in the second (results not shown). In agreement with the findings of Sandrucci et al (2014), the legs were the dirtiest part of the cows (on average 38·6 ± 3·42% of cows had a hygiene score >3). The cow udders showed, on average, a suboptimal level of cleanliness compared to previous studies (Sandrucci et al 2014), with a slight, but not significant, decrease in the percentage of udders with score >3 in the last experimental period when the complete milking routine was applied (25·8, 28·1 and 17·7% for the three periods, respectively; Table 2).…”
Section: Resultssupporting
confidence: 92%
“…There was an increase in the percentage of leg 3 + 4 scores from 27·1% in the first year to 49·9% in the second (results not shown). In agreement with the findings of Sandrucci et al (2014), the legs were the dirtiest part of the cows (on average 38·6 ± 3·42% of cows had a hygiene score >3). The cow udders showed, on average, a suboptimal level of cleanliness compared to previous studies (Sandrucci et al 2014), with a slight, but not significant, decrease in the percentage of udders with score >3 in the last experimental period when the complete milking routine was applied (25·8, 28·1 and 17·7% for the three periods, respectively; Table 2).…”
Section: Resultssupporting
confidence: 92%
“…Similar to present study, the gradual increase in SCC level with the advancement of stage of lactation have been observed in previous studies(Fadlelmoula et al, 2008; Ruegg and Pantoja, 2013) and stage of lactation was found as an important risk factor as cows in late lactation (>200 days in milk) had higher risk to have more SCC than cows in early and mid-lactation(Sandrucci et al, 2014). Increased SCC values towards the end of lactation could be due to higher infection rate as the teat streak canals aredilated due to continuous milking and dilution effect of increased milk yield during early lactation and declines of milk yield during mid and late lactation.…”
supporting
confidence: 91%
“…The increase in SCC observed for the cows with access to shade in stress period might be related to higher humidity at the ground with accumulated mud in the shaded area, conditions usually associated with high SCC (Sandrucci et al ., 2014). Also, a behavioral study (Vizzotto et al ., 2015) showed that cows with access to shade spent more time lying, increasing the udder's exposure to environmental pathogens, especially after milking.…”
Section: Discussionmentioning
confidence: 99%